The lateral joint line opening: a radiographic indicative parameter for high grade varus knees - William Colyn; A. Cleymans; L. Bruckers; R. Houben; K. Smeets; J. Bellemans (Journal of Experimental Orthopaedics)
Abstract Purpose It is usually assumed that the severity of varus osteoarthritis (OA) of the knee is correlated with the axis deviation of the limb. Despite this, there is currently no clear radiographic definition to define a so‐called ‘high degree’ varus knee, which is characterized by a pronounced lateral ligamentous laxity. The purpose of this study was to radiographically determine if the lateral joint line opening (LJLO) is an indicative parameter when defining so‐called high grade varus knees. Methods Two hundred forty Full length radiographs of patients with end‐stage varus osteoarthritis who were scheduled for Total knee arthroplasty (TKA) were evaluated. The Hip‐knee‐ankle‐angle (HKA‐angle), Joint‐line‐convergence‐angle (JLCA) and the lateral joint line opening were measured. The lateral joint line opening is the shortest distance between the lateral tibial plateau and the deepest point of the lateral femoral condyle. Linear regression models were used to investigate the relationships between the radiographic measurements. Results Hip‐knee‐angle‐angle, joint‐line‐conversion‐angle, and lateral joint line opening were all positively correlated (p < 0.001). An increase of 1 mm lateral joint line opening causes an increase of 0.6° joint‐line‐conversion‐angle (p = 0.029) below a cut‐off point of 4.7 mm. For lateral opening values beyond 4.7 mm, the gradient increased to 1.2 (p < 0.001). A lateral joint line opening of 4.7 mm corresponds to a hip‐knee‐ankle‐angle of 6.0° (95% CI [5.5; 6.5]). Conclusion A lateral joint line opening of more than 5 mm in end‐stage OA knees is indicative of increased lateral joint laxity. Those knees can be radiographically classified as so‐called ‘high‐grade’ varus knees. Level of evidence Therapeutic study, Level III.